Effects of elevated air temperature coupling with soil drought on carbohydrate metabolism and oil synthesis during cottonseed development. Issue 1 (23rd February 2022) - Xu, Bingjie; Hu, Wei; Gao, Min; Zhao, Wenqing; Wang, Youhua; Zhou, Zhiguo
Abstract: Cotton, as the fifth‐largest oilseed crop, often faces the coupling stress of heat and drought. Still, the effects of combined stress on cottonseed oil synthesis and its closely related carbon metabolism are poorly investigated. To this end, experiments were conducted with two cultivars (Sumian 15 and PHY370WR) under two temperature regimes: ambient temperature (AT) and elevated temperature (ET, which was 2.5°C–2.7°C higher than AT) and three water regimes: optimum soil moisture (soil relative water content [SRWC] at 75% ± 5%), and drought (SD) including SRWC 60% ± 5% and SRWC 45% ± 5%, during 2016–2018. Results showed that ET plus SD decreased cottonseed kernel yield, seed index, kernel weight, and kernel percentage more than either single stress. The content of hexoses, the carbon skeleton source for oil synthesis, was decreased by ET while increased by SD. The combined stress increased the hexose content by increasing the activities of sucrose synthase (SuSy, EC 2.4.1.13) and invertase (Inv, EC 3.2.1.26) and upregulating GhSuSy expression; however, hexose content under combined stress was lower than that under SD alone. Increased oil content under SD was attributed to the high phosphoenolpyruvate carboxylase (PEPCase, EC 4.1.1.31), acetyl‐CoA carboxylase (ACCase, EC 6.4.1.2), and diacylglycerol acyltransferase (DGAT, EC 2.3.1.20) activities, whereas the opposite effects were seen under ET. Under combined stress, although ACCase activity decreased, PEPCase and DGAT activities, and GhPEPC‐1 and GhDGAT‐1 expression upregulated, enhancing carbon flow into oil metabolism and triacylglycerol synthesis, ultimately generating higher oil content.